Proteolytic Bacterial Activity from the Digestive Tract of Udikan Fish (Tor Sp.) Caught in Banjaran River - Roni Ruswanda; Anandita Ekasanti; Rima Oktavia Kusuma (PT. Artha GenetikaLab Indonesia, 2025)
The type of feed commonly consumed by fish in nature can be predicted from the presence of microorganism communities in their digestive tract. One of the bacteria that plays an important role in the digestive tract is proteolytic bacteria. The purpose of this study was to determine the activity index and proportion of proteolytic bacteria from the digestive tract of udikan fish (Tor sp.) caught in the Banjaran River. The method used in this study was observation with a sampling technique conducted by purposive sampling. The activity index of proteolytic bacteria from the digestive tract of udikan fish (Tor sp.) was relatively low with an average value of 0.06 in 24-hour observations and 0.05 in 48-hour observations. The proportion of proteolytic bacteria obtained from the digestive tract of udikan fish (Tor sp.) was 33%.